Analisis Pengaruh Pendidikan dan Pelatihan Terhadap Kinerja Perangkat Desa pada Desa Pemepek - Muhamad Yunus; Zul Haeri; Neni Suryanirmala (Universitas Muhammadiyah Mataram, 2023)
This study aims to analyze the effect of education and training on the performance of village officials. This research was held in Pemepek Village, Pringgarata District, Central Lombok Regency. The sampling technique used in this study is Saturated Sampling. The sample in this study was employees of the Village Apparatus, which totaled 30 respondents. This research is a quantitative research and data analysis model using multiple linear regression. The results of this study show that partially in education and training research the calculated F value was obtained 9,061 while the F value of the table was 3.35, it can be known that the F value is calculated 9,061 > the F value of the table 3.35 with a significant level of 0.001 because the significant level < 0.05, then this regression model can be used for performance variables at the pekpek village office, in other words, it can be said that the variables of education and training together (simultaneously) have an effect on significant to performance.